Curable composition, cured product thereof, LED element, electronic device, and optical element

A solvent-free curable composition, suitable for inkjet application and without annealing, addresses the challenges of LED sealing by providing a cured product with enhanced heat, light, and moisture resistance, along with excellent transparency and adhesion.

JP7666751B2Active Publication Date: 2025-04-22DIC CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024541842
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-01-20
Filing Date
2023-09-21
Publication Date
2025-04-22
Estimated Expiration
2043-09-21

AI Technical Summary

Technical Problem

Existing LED sealing materials struggle to provide simultaneous transparency, adhesion, heat resistance, light resistance, and moisture resistance, especially for high-output LEDs and micro LED displays, while also requiring solvent-based compositions and annealing processes.

Method used

A curable composition comprising (meth)acrylates with hydroxy groups, (meth)acrylates with phosphate groups, and monomers with two or more (meth)acrylate groups, which can be formulated to be solvent-free and applied via the inkjet method without the need for annealing.

Benefits of technology

The curable composition achieves excellent curability and storage stability, forming a cured product with superior heat resistance, light resistance, moisture resistance, transparency, and adhesion to the substrate, making it suitable for high-performance LED sealing applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666751000004
    Figure 0007666751000004
  • Figure 0007666751000001
    Figure 0007666751000001
  • Figure 0007666751000002
    Figure 0007666751000002
Patent Text Reader

Abstract

Provided is a curable composition which exhibits excellent curing properties and storage stability and with which a cured product having excellent heat resistance, light resistance, moisture resistance, transparency, and adhesion to a substrate can be formed using an inkjet method. Provided is a curable composition that contains, as essential components, a hydroxyl group-containing (meth)acrylate (a) and a monomer (c) having two or more (meth)acrylate groups. Also provided are: an LED sealing material that is a cured product of said curable composition; an LED element containing a cured product of said curable composition; and an electronic device and optical element that are obtained using a cured product of said curable composition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable composition, a cured product of the curable composition, an LED element containing the cured product, an electronic device using the cured product, and an optical element using the cured product. [Background technology]

[0002] Display devices such as liquid crystal displays, plasma displays, organic electroluminescence displays, mini LED displays, etc. are widely used. In recent years, there has been active development towards the practical application of micro LED displays, which have excellent characteristics such as brightness, color gamut, contrast, and reliability, and can achieve low power consumption by using highly efficient LEDs as the light source. From the viewpoint of maintaining the characteristics of light-emitting elements, various sealing materials have been developed. Patent Document 1 discloses a method of sealing an organic light-emitting material layer and electrodes constituting an organic EL display element with a laminated film of a silicon nitride film and a resin film formed by a CVD method in order to suppress deterioration of the characteristics of the organic EL element due to moisture, oxygen, etc. In addition, heat generation from LED packages accompanying the increase in LED output has become a problem, and silicone-based resins have been used as LED sealing materials instead of epoxy resins, which inevitably turn yellow. Patent Document 2 discloses a thermosetting resin composition containing a thermosetting resin composed of a specific silsesquioxane and an organopolysiloxane, a cured product thereof, and a composition for optical semiconductors containing the thermosetting resin composition. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2000-223264 A [Patent Document 2] International Publication No. 2014 / 077216 Summary of the Invention [Problem to be solved by the invention]

[0004] In electronic devices using light-emitting elements such as LEDs, for example backlights and displays, encapsulants are required to have reliability such as heat resistance against heat generation and light emitted by the light-emitting elements, light resistance, and moisture resistance in high humidity environments, as well as properties such as transparency and adhesion. As the requirements for LED encapsulants are becoming increasingly strict, there is a demand for transparent encapsulants that can meet the needs of higher output LEDs and higher performance in micro LED displays and the like, that combine heat resistance, light resistance, and moisture resistance, and that have excellent adhesion to substrates, but there is still room for improvement. On the other hand, with regard to the composition itself as an encapsulant, from the viewpoints of not only the production costs of the compounds to be blended, but also environmental considerations, responding to the trend toward thinner displays, and further simplifying the production process and improving safety, there is a demand for a solvent-free composition that can be applied by an inkjet method and does not require an annealing treatment.

[0005] Means for Solving the Problems The present inventors have conducted extensive research and found that a curable composition containing a specific polymerizable monomer as a constituent component has excellent curability, can be used to form a molded product by an inkjet method, and has excellent physical properties such as heat resistance, light resistance, moisture resistance, and transparency. An object of the present invention is to provide a curable composition which has excellent curability and storage stability, and which can be used to form a cured product by an inkjet method, which has excellent heat resistance, light resistance, moisture resistance, transparency, and adhesion to a substrate. Another object of the present invention is to provide an LED encapsulant that is a cured product of the curable composition, an LED element that includes the cured product of the curable composition, and an electronic device and an optical element that use the cured product of the curable composition. [Means for solving the problem]

[0006] The present invention has the following aspects. [1] A curable composition comprising, as essential components, a (meth)acrylate having a hydroxyl group (a) and a monomer having two or more (meth)acrylate groups (c). [2] A curable composition comprising the following components (a) to (c) as essential components: (Meth)acrylate having a hydroxy group (a) (Meth)acrylate having a phosphate group (b) (c) a monomer having two or more (meth)acrylate groups [3] The curable composition according to [1] or [2], further comprising a (meth)acrylate having a cyclic skeleton (d). [4] The curable composition according to [3], wherein the (meth)acrylate having a cyclic skeleton (d) is at least one selected from the group consisting of (d1) (meth)acrylates having a cyclic skeleton containing a heteroatom and (d2) (meth)acrylates having a carbon ring skeleton. [5] The curable composition according to any one of [1] to [4], comprising the monomer (c) having two or more (meth)acrylate groups in an amount of 5 to 50 mass % based on the total mass of the composition. [6] The curable composition according to any one of [1] to [5], wherein the monomer (c) having two or more (meth)acrylate groups is a monomer having three or more (meth)acrylate groups. [7] The curable composition according to any one of [1] to [6], wherein the (meth)acrylate (a) having a hydroxy group is contained in an amount of 10 to 50 mass % based on the total mass of the composition. [8] The curable composition according to any one of [2] to [7], wherein the (meth)acrylate having a phosphate group (b) is contained in an amount of 0.01 to 10 mass % relative to the total mass of the composition. [9] The curable composition according to any one of [1] to [8], further comprising a photopolymerization initiator.

[10] The curable composition according to any one of [1] to [9], which is an active energy ray-curable composition.

[11] Any of the curable compositions of [1] to

[10] , having a viscosity at 25°C of 3 to 30 mPa s.

[12] The curable composition according to any one of [1] to

[11] , which does not contain a solvent.

[13] The curable composition according to any one of [1] to

[12] , which is a composition for an LED encapsulant.

[14] The curable composition according to any one of [1] to

[13] , which is formed by an inkjet method.

[15] A cured product of the curable composition according to any one of [1] to

[14] .

[16] The cured product of

[15] , which is an LED encapsulant.

[17] An LED element comprising a cured product of the curable composition according to any one of [1] to

[14] .

[18] An electronic device using a cured product of the curable composition according to any one of [1] to

[14] .

[19] An optical element using a cured product of the curable composition according to any one of [1] to

[14] . Effect of the Invention

[0007] According to the present invention, there can be provided a curable composition that is excellent in curability and storage stability, and that can form a cured product by an inkjet method that is excellent in heat resistance, light resistance, moisture resistance, transparency, and adhesion to a substrate. Furthermore, according to the present invention, there can be provided an LED encapsulant that is a cured product of the curable composition, an LED element that includes a cured product of the curable composition, and an electronic device and an optical element that use a cured product of the curable composition. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a diagram illustrating a configuration example of a micro LED display as one embodiment of an electronic device using a cured product of the curable composition of the present invention as an encapsulant. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention is a curable composition comprising, as essential components, a (meth)acrylate having a hydroxy group (a) and a monomer having two or more (meth)acrylate groups (c). The present invention also relates to a curable composition comprising the following components (a) to (c) as essential components: (Meth)acrylate having a hydroxy group (a) (Meth)acrylate having a phosphate group (b) (c) a monomer having two or more (meth)acrylate groups Hereinafter, the curable composition of the present invention may also be simply referred to as "the present curable composition." The present curable composition preferably further contains a (meth)acrylate having a cyclic skeleton (d), and the (meth)acrylate having a cyclic skeleton (d) is preferably at least one selected from the group consisting of (meth)acrylates having a cyclic skeleton containing a hetero atom (d1) and (meth)acrylates having an aromatic ring (d2). In this specification, "(meth)acrylate" is a term that collectively refers to acrylate, methacrylate, and both. "(meth)acrylic" is a term that collectively refers to acrylic, methacrylic, and both. "(meth)acryloyloxy group" is a term that collectively refers to acryloyloxy group, methacryloyloxy group, and both.

[0010] The present curable composition has excellent curability and storage stability. In addition, the present curable composition can be used to form a cured product by an inkjet method, which has excellent heat resistance, light resistance, moisture resistance, transparency, and adhesion to a substrate. The constitution of the present curable composition will be described below.

[0011] Examples of the (meth)acrylate (a) having a hydroxy group in the present curable composition include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-ethylhexyl diglycol (meth)acrylate, diethylene glycol mono(meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 1,4-cyclohexanedimethanol monoacrylate, 1-(acryloyloxy)-3-(methacryloyloxy)-2-propanol, pentaerythritol triacrylate, etc. Among these, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and pentaerythritol triacrylate are preferred, and 4-hydroxybutyl acrylate is more preferred, from the viewpoints of being versatile, relatively inexpensively available, and excellent in various physical properties such as good curability, inkjet dischargeability, and moisture resistance and heat resistance of the cured product after curing. By including the (meth)acrylate (a) having a hydroxy group, the moisture resistance and heat resistance of the cured product formed from the present curable composition are improved.

[0012] The content of the (meth)acrylate (a) having a hydroxyl group in the present curable composition is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more, based on the total mass of the present curable composition. The content of the (meth)acrylate (a) having a hydroxyl group is preferably 50% by mass or less, more preferably 45% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less, based on the total mass of the present curable composition. In other words, the content of the (meth)acrylate (a) having a hydroxyl group in the present curable composition is preferably in the range of 10 to 50% by mass, more preferably 15 to 45% by mass, more preferably 20 to 40% by mass, and even more preferably 20 to 35% by mass, based on the total mass of the present curable composition. When the present curable composition contains the (meth)acrylate (a) having a hydroxy group in the above range, the present curable composition has good curability, and the storage stability of the curable composition and the performance of the cured product after curing, such as moisture resistance and heat resistance, are improved. In addition, the performance of the cured product formed from the present curable composition, such as adhesion to a substrate, is improved.

[0013] In the present curable composition, examples of the (meth)acrylate (b) having a phosphate group include alkylene (meth)acrylate phosphates such as methylene (meth)acrylate phosphate, ethylene (meth)acrylate phosphate, propylene (meth)acrylate phosphate, and tetramethylene (meth)acrylate phosphate; phosphate esters of polyethylene glycol monoacrylate; and phosphate esters of polypropylene glycol monomethacrylate; or compounds containing a phosphate ester represented by the following general formula (b1).

[0014] [ka]

[0015] [In formula (b1), R 1 R represents a hydrogen atom or a methyl group. 2 R represents a linear or branched alkylene group having 1 to 4 carbon atoms. 3 represents a divalent organic group. s is an integer of 0 to 3, t is an integer of 1 to 6, and u is a positive number of 1 to 2.]

[0016] R in general formula (b1) 2 is preferably a linear or branched alkylene group having 2 or 3 carbon atoms, and examples thereof include a methylene group [-CH-], an ethylene group [-(CH)-], a trimethylene group [-(CH)-], -CH(CH)-, -CH(CHCH)-, and -C(CH)-.

[0017] R in general formula (b1) 3Examples of the divalent organic group represented by include a saturated or unsaturated divalent aliphatic hydrocarbon group having 1 to 12 carbon atoms, a divalent aromatic hydrocarbon group having 6 to 12 carbon atoms, and a divalent linking group containing a hetero atom. These groups may have a substituent. Examples of the substituent include a fluorine atom, a fluorinated alkyl group having 1 to 5 carbon atoms and substituted with a fluorine atom, and a carbonyl group. The divalent aliphatic hydrocarbon group may be linear or branched, and examples of such groups include alkylene groups such as methylene, ethylene, trimethylene, tetramethylene [-(CH2)4-] and pentamethylene [-(CH2)5-]; alkylmethylene groups such as -CH(CH3)-, -CH(CH2CH3)-, -C(CH3)2-, -C(CH3)(CH2CH3)-, -C(CH3)(CH2CH2CH3)- and -C(CH2CH3)2-; Examples of alkyl alkylene groups include alkyl ethylene groups such as -CH3)CH2-, -CH(CH3)CH(CH3)-, -C(CH3)2CH2-, -CH(CH2CH3)CH2-, -C(CH2CH3)2-CH2-, etc.; alkyl trimethylene groups such as -CH(CH3)CH2CH2- and -CH2CH(CH3)CH2-, etc.; and alkyl tetramethylene groups such as -CH(CH3)CH2CH2CH2- and -CH2CH(CH3)CH2CH2-, etc. Examples of the divalent linking group containing a hetero atom include -O-, -C(=O)-O-, -OC(=O)-, -C(=O)-, -OC(=O)-O-, -C(=O)-NH-, -NH-, -S-, -S(=O)2-, and -S(=O)2-O-. Among them, R 3 is preferably a linear or branched alkylene group, an ester bond [-C(=O)-O-, -OC(=O)-], an ether bond (-O-), or a combination thereof.

[0018] Specific examples of the (meth)acrylate (b) having a phosphate group represented by general formula (b1) are shown below. 1 and u is as defined above.

[0019] [ka]

[0020] The (meth)acrylate (b) having a phosphate group may be a commercially available product, such as "EBECRYL168" manufactured by Daicel-Allnex Co., Ltd., "KAYAMER PM-2" and "KAYAMER PM-21" manufactured by Nippon Kayaku Co., Ltd., "Hosmer M", "Hosmer PE", and "Hosmer PP" manufactured by Unichemical Co., Ltd., "Light Ester P-1M", "Light Acrylate P-1A(N)", and "Light Ester P-2M" manufactured by Kyoeisha Chemical Co., Ltd., and "JPA-514" manufactured by Johoku Chemical Industry Co., Ltd.

[0021] The (meth)acrylate (b) having a phosphoric acid group may be used alone or in combination of two or more kinds. When the present curable composition contains a (meth)acrylate (b) having a phosphoric acid group, the content is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, more preferably 0.03% by mass or more, more preferably 0.05% by mass or more, more preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.5% by mass or more, based on the total mass of the present curable composition. The content of the (meth)acrylate (b) having a phosphoric acid group is preferably 10% by mass or less, more preferably 8% by mass or less, more preferably 8% by mass or less, more preferably 5% by mass or less, more preferably 3% by mass or less, more preferably 2% by mass or less, more preferably 1% by mass or less, and even more preferably 0.8% by mass or less, based on the total mass of the present curable composition. In other words, when the present curable composition contains the (meth)acrylate (b) having a phosphate group, the content thereof is preferably in the range of 0.01 to 10 mass%, more preferably in the range of 0.02 to 8 mass%, and even more preferably in the range of 0.03 to 5 mass%, relative to the total mass of the present curable composition. When the present curable composition contains the (meth)acrylate (b) having a phosphate group in the above range, the present curable composition has good curability, and the performance of the cured product formed from the present curable composition, such as adhesion to a substrate, is improved.

[0022] In the present curable composition, examples of the monomer (c) having two or more (meth)acrylate groups include ethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 2-methyl-1,8-octanediol di(meth)acrylate, 2-butyl- glycol di(meth)acrylates such as 2-ethyl-1,3-propanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, ethoxylated (2) neopentyl glycol di(meth)acrylate [a compound obtained by di(meth)acrylating a 2-mol adduct of neopentyl glycol ethylene oxide], and propoxylated (2) neopentyl glycol di(meth)acrylate [a compound obtained by di(meth)acrylating a 2-mol adduct of neopentyl glycol propylene oxide];

[0023] Alkylene glycol di(meth)acrylates such as diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetrapropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, and bis(4-acryloxypolyethoxyphenyl)propane; Di(meth)acrylate of tris(2-hydroxyethyl)isocyanurate; Dimethyloltricyclodecane di(meth)acrylate, caprolactone-modified hydroxypivalic acid neopentyl glycol di(meth)acrylate; Bisphenol A di(meth)acrylate, propylene oxide modified bisphenol A di(meth)acrylate, ethylene oxide modified bisphenol A di(meth)acrylate, bisphenol F di(meth)acrylate, propylene oxide modified bisphenol F di(meth)acrylate, ethylene oxide modified bisphenol F di(meth)acrylate; trifunctional (meth)acrylates such as pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane ethylene oxide modified tri(meth)acrylate, trimethylolpropane propylene oxide modified tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, modified glycerin tri(meth)acrylate, propylene oxide adduct of glycerin tri(meth)acrylate, and ethylene oxide adduct of glycerin tri(meth)acrylate; tetrafunctional (meth)acrylates such as pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, and tetramethylolmethane tetra(meth)acrylate; hexafunctional (meth)acrylates such as dipentaerythritol hexa(meth)acrylate and caprolactone-modified dipentaerythritol hexa(meth)acrylate; and the like.

[0024] The monomer (c) having two or more (meth)acrylate groups may be used alone or in combination of two or more. The content of the monomer (c) having two or more (meth)acrylate groups in the present curable composition is preferably 5% by mass or more, more preferably 8% by mass or more, and even more preferably 10% by mass or more, based on the total mass of the present curable composition. The content of the monomer (c) having two or more (meth)acrylate groups is preferably 50% by mass or less, more preferably 45% by mass or less, more preferably 40% by mass or less, more preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less, based on the total mass of the present curable composition. In other words, the content of the monomer (c) having two or more (meth)acrylate groups in the present curable composition is preferably in the range of 5 to 50% by mass, more preferably in the range of 5 to 45% by mass, more preferably in the range of 5 to 40% by mass, more preferably in the range of 5 to 30% by mass, more preferably in the range of 5 to 20% by mass, and even more preferably in the range of 5 to 15% by mass, based on the total mass of the present curable composition. When the present curable composition contains the monomer (c) having two or more (meth)acrylate groups within the above range, the present curable composition has good curability, and the cured product formed from the present curable composition has improved performance such as flexibility and adhesion to a substrate. In addition, when one type of compound is used alone as the monomer (c) having two or more (meth)acrylate groups, the use of a monomer having three or more (meth)acrylate groups, such as the above-exemplified trifunctional (meth)acrylates and tetrafunctional (meth)acrylates, e.g., trimethylolpropane ethylene oxide-modified triacrylate, can effectively improve the performance of the cured product formed from the present curable composition, such as flexibility and adhesion to a substrate. When two or more compounds are used in combination as the monomer (c) having two or more (meth)acrylate groups, it is preferable to use a monomer having three or more (meth)acrylate groups, such as the trifunctional (meth)acrylate or tetrafunctional (meth)acrylate exemplified above, in order to effectively improve the flexibility of the cured product formed from the present curable composition and the performance of the adhesiveness to the substrate, etc. In this case, the content of the monomer having three or more (meth)acrylate groups in the monomer (c) having two or more (meth)acrylate groups is preferably 10 mass% or more, and the total amount may be monomers having three or more (meth)acrylate groups.

[0025] The present curable composition may further contain a (meth)acrylate (d) having a cyclic skeleton. When the present curable composition contains a (meth)acrylate (d) having a cyclic skeleton, it becomes easy to adjust the viscosity of the present curable composition to a suitable viscosity range when molding by the inkjet method. In addition, the shrinkage of the cured product formed from the present curable composition is small, and the adhesiveness is excellent. From these viewpoints, it is preferable to further contain a (meth)acrylate (d) having a cyclic skeleton. In this specification, a (meth)acrylate having a hydroxyl group and a cyclic skeleton is classified as a (meth)acrylate having a hydroxyl group (a), and a (meth)acrylate having a phosphate group and a cyclic skeleton is classified as a (meth)acrylate having a phosphate group (b). A monomer having two or more (meth)acrylate groups is classified as a (meth)acrylate having a hydroxyl group (a) or a (meth)acrylate having a phosphate group (b) if it has at least one of a hydroxyl group or a phosphate group, regardless of whether it has a cyclic skeleton or not, and is classified as a monomer having two or more (meth)acrylate groups (c) if it has neither a hydroxyl group nor a phosphate group. In other words, the (meth)acrylate (d) having a cyclic skeleton includes a mono(meth)acrylate having a cyclic skeleton and having neither a hydroxyl group nor a phosphoric acid group.

[0026] The (meth)acrylate having a cyclic skeleton (d) is preferably at least one selected from the group consisting of (d1) (meth)acrylates having a cyclic skeleton containing a hetero atom and (d2) (meth)acrylates having a carbon ring skeleton. Examples of the (meth)acrylate (d1) having a cyclic skeleton containing a hetero atom include (meth)acryloylmorpholine, N-(meth)acryloyloxyethylhexahydrophthalimide, tetrahydrofurfuryl (meth)acrylate, and cyclic trimethylolpropane formal (meth)acrylate.

[0027] Examples of the (meth)acrylate (d2) having a carbon ring skeleton include mono(meth)acrylates having a cyclic aliphatic group, such as cyclohexyl (meth)acrylate, 4-t-butylcyclohexyl (meth)acrylate, tricyclodecane dimethanol mono(meth)acrylate, adamantyl (meth)acrylate, cyclohexane dimethanol mono(meth)acrylate, trimethylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and dicyclopentenyloxyethyl (meth)acrylate; and mono(meth)acrylates having an aromatic hydrocarbon group, such as 2-phenoxyethyl (meth)acrylate and benzyl (meth)acrylate.

[0028] The (meth)acrylate (d) having a cyclic skeleton may be used alone or in combination of two or more. From the viewpoint of excellent heat resistance of the cured product after curing, it is preferable that the (meth)acrylate (d) having a cyclic skeleton contains a (meth)acrylate (d2) having a carbon ring skeleton. In particular, when the present curable composition does not contain a (meth)acrylate (b) having a phosphoric acid group but contains a (meth)acrylate (d) having a cyclic skeleton, the content of the (meth)acrylate (d2) having a carbon ring skeleton in the (meth)acrylate (d) having a cyclic skeleton is preferably 50 mass% or more, and the total amount may be the (meth)acrylate (d2) having a carbon ring skeleton. From the viewpoints of excellent safety, general-purpose availability, and relatively inexpensive availability, and excellent physical properties such as inkjet ejection properties, good curing properties, and adhesion of the cured product to a substrate after curing, tetrahydrofurfuryl (meth)acrylate and cyclic trimethylolpropane formal (meth)acrylate are more preferable as the (meth)acrylate (d1) having a cyclic skeleton containing a hetero atom, and 2-phenoxyethyl (meth)acrylate, isobornyl (meth)acrylate, 3,3,5-trimethylcyclohexyl acrylate, and t-butylcyclohexyl acrylate are more preferable as the (meth)acrylate (d2) having a carbon ring skeleton. In the present curable composition, it is more preferable to use, as the (meth)acrylate (d) having a cyclic skeleton, two or more of the following four compounds: tetrahydrofurfuryl acrylate, cyclic trimethylolpropane formal acrylate, 2-phenoxyethyl acrylate, and 3,3,5-trimethylcyclohexyl acrylate.

[0029] When the present curable composition contains a (meth)acrylate (d) having a cyclic skeleton, the content is preferably 30% by mass or more, more preferably 35% by mass or more, more preferably 40% by mass or more, more preferably 45% by mass or more, and even more preferably 50% by mass or more, based on the total mass of the present curable composition. The content of the (meth)acrylate (d) having a cyclic skeleton is preferably 80% by mass or less, more preferably 75% by mass or less, even more preferably 70% by mass or less, even more preferably 65% ​​by mass or less, and particularly preferably 60% by mass or less, based on the total mass of the present curable composition. In other words, when the present curable composition contains a (meth)acrylate (d) having a cyclic skeleton, the content is preferably in the range of 30 to 80% by mass, more preferably in the range of 30 to 70% by mass, more preferably in the range of 40 to 70% by mass, more preferably in the range of 50 to 70% by mass, and even more preferably in the range of 50 to 65% by mass, based on the total mass of the present curable composition. When the ink composition contains the (meth)acrylate (d) having a cyclic skeleton within the above range, the curable composition has good curability, and the storage stability and the performance of the cured product formed are improved. In addition, when the (meth)acrylate having a cyclic skeleton (d) contains both a (meth)acrylate having a heteroatom (d1) and a (meth)acrylate having a carbon ring skeleton (d2), the content ratio thereof is not particularly limited, but from the viewpoint of excellent physical properties such as inkjet dischargeability, good curability, and adhesion of the cured product to a substrate after curing, the proportion of the (meth)acrylate having a heteroatom (d1) is preferably 50 mass% or more, and from the viewpoint of excellent heat resistance of the cured product after curing, the proportion of the (meth)acrylate having a carbon ring skeleton (d2) in the (meth)acrylate having a cyclic skeleton (d) is preferably 50 mass% or more. In particular, in order to obtain a good balance of good inkjet dischargeability, good curability, good adhesion of the cured product to a substrate after curing, and excellent heat resistance of the cured product after curing, the proportion of the (meth)acrylate (d2) having a carbon ring skeleton in the (meth)acrylate (d) having a cyclic skeleton is preferably in the range of 20 to 70 mass%, more preferably in the range of 25 to 70 mass%, and even more preferably in the range of 30 to 65 mass%.

[0030] The present curable composition may further contain other polymerizable compounds different from the above-mentioned (a) (meth)acrylate having a hydroxy group, (b) (meth)acrylate having a phosphoric acid group, (c) monomer having two or more (meth)acrylate groups, and (d) (meth)acrylate having a cyclic skeleton. Other polymerizable compounds include monofunctional polymerizable compounds and polymerizable compounds having two or more polymerizable groups (hereinafter referred to as "polyfunctional polymerizable compounds"). Here, the polymerizable group means a group having a polymerizable unsaturated double bond.

[0031] The above-mentioned monofunctional polymerizable compound is preferably a compound having a polymerizable unsaturated double bond and being liquid at 25° C., and its molecular weight is preferably 60 to 2,000, and more preferably 100 to 1,000. The viscosity of the monofunctional polymerizable compound is preferably 1000 mPa·s or less, more preferably 300 mPa·s or less, and more preferably 1 mPa·s or more, more preferably 3 mPa·s or more.

[0032] Examples of the monofunctional polymerizable compound that is the other polymerizable compound include a polymerizable compound having a heterocyclic structure, a monofunctional (meth)acrylate having a chain-like aliphatic group, a monofunctional (meth)acrylate having an alkyleneoxy group, and a monovinyl ether compound. Examples of the polymerizable compound having a heterocyclic structure include N-vinylcaprolactam, N-vinylpyrrolidone, and N-vinylformamide. Examples of monofunctional (meth)acrylates having a chain aliphatic group include isoamyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, decyl (meth)acrylate, isomyristyl (meth)acrylate, and isostearyl (meth)acrylate.

[0033] Examples of monofunctional (meth)acrylates having an alkyleneoxy group include methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, ethoxyethoxyethyl (meth)acrylate, diethylene glycol monobutyl ether (meth)acrylate, methoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and methoxypropylene glycol (meth)acrylate.

[0034] Examples of the monovinyl ether compound include ethylene glycol monovinyl ether, triethylene glycol monovinyl ether, hydroxyethyl monovinyl ether, ethyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, octadecyl vinyl ether, cyclohexyl vinyl ether, hydroxybutyl vinyl ether, 2-ethylhexyl vinyl ether, hydroxynonyl monovinyl ether, cyclohexanedimethanol monovinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, isopropenyl vinyl ether, dodecyl vinyl ether, diethylene glycol monovinyl ether, phenyl glycidyl ether, butyl glycidyl ether, and 2-ethylhexyl glycidyl ether.

[0035] The polyfunctional polymerizable compound, which is the other polymerizable compound, may be any one of a monomer, an oligomer, and a polymer. In this specification, the term "monomer" means a compound having a molecular weight (weight average molecular weight when it has a molecular weight distribution) of 1000 or less. The molecular weight of the monomer (weight average molecular weight when it has a molecular weight distribution) is 50 to 1000. The term "oligomer" generally means a polymer having a finite number of monomer-based constituent units (generally 5 to 100) and a weight average molecular weight of more than 1000 and less than 30000. The term "polymer" means a polymer having a weight average molecular weight of 30000 or more. The weight average molecular weight is a value measured by gel permeation chromatography (GPC) and calculated as a standard polystyrene equivalent value.

[0036] The polyfunctional polymerizable compound may be a compound represented by the following general formula (1): CH2=CR 4 -COO-R 5 -O-CH=CH-R 6 (1) (In the formula, R 4 represents a hydrogen atom or a methyl group, R 5 represents an organic residue having 2 to 20 carbon atoms, and R 6represents a hydrogen atom or an organic residue having 1 to 11 carbon atoms.) (hereinafter simply referred to as "monomer (1)"), divinyl ether compounds, trivinyl ether compounds, urethane (meth)acrylates, and amino (meth)acrylates.

[0037] In general formula (1), R 5 Examples of the organic residue having 2 to 20 carbon atoms represented by the formula (I) include a linear, branched or cyclic alkylene group having 2 to 20 carbon atoms, an alkylene group having 2 to 20 carbon atoms having an oxygen atom in its structure via an ether bond and / or an ester bond, and an aromatic group having 6 to 11 carbon atoms in which a hydrogen atom bonded to a carbon atom constituting the ring may be substituted with another substituent, and an alkylene group having 2 to 6 carbon atoms and an alkylene group having 2 to 9 carbon atoms having an oxygen atom in its structure via an ether bond are preferred. R 6 Examples of the organic residue having 1 to 11 carbon atoms represented by the formula (1) include a linear, branched or cyclic alkyl group having 1 to 10 carbon atoms, and an aromatic group having 6 to 11 carbon atoms in which a hydrogen atom bonded to a carbon atom constituting the ring may be substituted with another substituent, and an alkyl group having 1 to 2 carbon atoms and an aromatic group having 6 to 8 carbon atoms are preferred.

[0038] Specific examples of monomer (1) include 2-vinyloxyethyl (meth)acrylate, 3-vinyloxypropyl (meth)acrylate, 1-methyl-2-vinyloxyethyl (meth)acrylate, 2-vinyloxypropyl (meth)acrylate, 4-vinyloxybutyl (meth)acrylate, 1-methyl-3-vinyloxypropyl (meth)acrylate, 1-vinyloxymethylpropyl (meth)acrylate, 2-methyl-3-vinyloxypropyl (meth)acrylate, 3-methyl-3-vinyloxypropyl (meth)acrylate, and the like. (meth)acrylate, 1,1-dimethyl-2-vinyloxyethyl, (meth)acrylate, 3-vinyloxybutyl, (meth)acrylate, 1-methyl-2-vinyloxypropyl, (meth)acrylate, 2-vinyloxybutyl, (meth)acrylate, 4-vinyloxycyclohexyl, (meth)acrylate, 5-vinyloxypentyl, (meth)acrylate, 6-vinyloxyhexyl, (meth)acrylate, 4-vinyloxymethylcyclohexylmethyl, (meth)acrylate, p-vinyloxymethylphenyl Methyl, 2-(vinyloxyethoxy)ethyl (meth)acrylate, 2-(vinyloxyisopropoxy)ethyl (meth)acrylate, 2-(vinyloxyethoxy)propyl (meth)acrylate, 2-(vinyloxyethoxy)isopropyl (meth)acrylate, 2-(vinyloxyisopropoxy)propyl (meth)acrylate, 2-(vinyloxyisopropoxy)isopropyl (meth)acrylate, 2-(vinyloxyethoxyethoxy)ethyl (meth)acrylate, 2-(vinyloxy Examples of the monomer (1) include 2-(vinyloxyethoxyisopropoxy)ethyl (meth)acrylate, 2-(vinyloxyethoxyisopropoxy)propyl (meth)acrylate, 2-(vinyloxyethoxyethoxy)isopropyl (meth)acrylate, 2-(vinyloxyethoxyisopropoxy)isopropyl (meth)acrylate, 2-(vinyloxyethoxyethoxyethoxy)ethyl (meth)acrylate, polyethylene glycol monovinyl ether (meth)acrylate, and polypropylene glycol monovinyl ether (meth)acrylate. As the monomer (1), from the viewpoints of low viscosity, high flash point, and excellent curability, 2-(2-vinyloxyethoxy)ethyl (meth)acrylate is preferred, and 2-(2-vinyloxyethoxy)ethyl acrylate is more preferred.

[0039] Examples of the divinyl ether compound or trivinyl ether compound include ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, propylene glycol divinyl ether, dipropylene glycol divinyl ether, butanediol divinyl ether, hexanediol divinyl ether, cyclohexanedimethanol divinyl ether, and trimethylolpropane trivinyl ether.

[0040] Examples of the urethane (meth)acrylate include aliphatic urethane (meth)acrylate and aromatic urethane (meth)acrylate. The weight average molecular weight of the urethane (meth)acrylate is preferably 1000 to 30000, more preferably 2000 to 20000. The urethane (meth)acrylate may be a commercially available product, such as U-2PPA, U-4HA, U-6HA, U-6LPA, U-15HA, U-324A, UA-122P, UA5201, UA-512, etc., manufactured by Shin-Nakamura Chemical Co., Ltd.; and CN965NS, CN964A85, CN964, CN959, CN962, CN963J85, CN965, CN982B8, etc., manufactured by Sartomer. 8, CN981, CN983, CN996, CN9002, CN9007, CN9009, CN9010, CN9011, CN9178, CN9788, CN9893; and EBECRYL230, EBECRYL270, EBECRYL8402, EBECRYL8804, EBECRYL8807, EBECRYL9270, KRM8191, and the like manufactured by Daicel-Allnex Co., Ltd.

[0041] The amino(meth)acrylate is an amine-modified (meth)acrylate having an amino group. The number average molecular weight of the amino(meth)acrylate is preferably 2000 to 20000, more preferably 2000 to 10000, and further preferably 2000 to 5000. As the amino(meth)acrylate, a commercially available product may be used, and examples thereof include EBECRYL7100 and EBECRYL80 manufactured by Daicel-Allnex Corporation.

[0042] When the present curable composition further contains another polymerizable compound, the other polymerizable compound may be used alone or in combination of two or more. When the present curable composition further contains another polymerizable compound, the content is preferably 30 mass% or less, more preferably 20 mass% or less, and even more preferably 10 mass% or less, based on the entire present curable composition, from the viewpoint of easy adjustment of the viscosity of the present curable composition obtained and easy adjustment of the cure shrinkage rate of the cured product of the present curable composition.

[0043] The present curable composition may be a curable composition that is cured by heat, or a curable composition that is cured by active energy rays.From the viewpoint of more suitable use as an LED encapsulant, as described later, the present curable composition is preferably a curable composition that is cured by active energy rays.For this reason, the present curable composition may further include a photopolymerization initiator, and preferably includes a photopolymerization initiator.

[0044] Examples of the photopolymerization initiator include acylphosphine compounds such as 2-methylbenzoyldiphenylphosphine oxide, bis(2,6-dichlorobenzoyl)phenylphosphine oxide, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide; phosphinic acid ester compounds such as methyl (2,4,6-trimethylbenzoyl)phenylphosphinate, ethyl (2,4,6-trimethylbenzoyl)phenylphosphinate, methyl (3-benzoyl-2,4,6-trimethylbenzoyl)phenylphosphinate, ethyl (3-benzoyl-2,4,6-trimethylbenzoyl)phenylphosphinate, and isopropyl pivaloylphenylphosphinate; Benzoin isobutyl ether, 2,4-diethylthioxanthone [also called 2,4-diethylthioxanthen-9-one], 2-isopropylthioxanthone, methylbenzoyl formate, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 1-hydroxycyclohexyl phenyl ketone, benzoin ethyl ether, benzyl dimethyl ketal, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methyl propan-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, benzophenone, 4-phenylbenzophenone, isophthalphenone, 4-benzoyl-4'-methyldiphenyl sulfide, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-(4-morpholinophenyl)-butan-1-one), 1-{4-[(4-benzoylphenyl)sulfanyl]phenyl}-2-methyl-2-[(4-methylphenyl)sulfonyl]propan-1-one, and the like.

[0045] Among these, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, (2,4,6-trimethylbenzoyl)phenylphosphinate ethyl, and (3-benzoyl-2,4,6-trimethylbenzoyl)phenylphosphinate ethyl are preferred, which correspond to the wavelength of light emitted from an ultraviolet light-emitting diode (UV-LED) light source as a light source of active energy rays. In particular, when a UV-LED with a main peak wavelength of 365 to 405 nm is used as a light source, it is preferred to use an acylphosphine compound, particularly phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide or (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, as a photopolymerization initiator.

[0046] The photopolymerization initiator may be contained alone or in combination of two or more kinds. When the present curable composition contains a photopolymerization initiator, the content is preferably 1 to 10 mass %, more preferably 2 to 8 mass %, based on the entire present curable composition. When the content of the photopolymerization initiator is within the above range, the present curable composition has good curability and storage stability, and the coloring of the formed cured product is suppressed, tending to improve the performance of the cured product.

[0047] When the present curable composition contains a photopolymerization initiator, the present curable composition may further contain a sensitizer. Examples of the sensitizer include trimethylamine, methyldimethanolamine, triethanolamine, p-diethylaminoacetophenone, ethyl p-dimethylaminobenzoate, isoamyl p-dimethylaminobenzoate, N,N-dimethylbenzylamine, 4,4'-bis(diethylamino)benzophenone, anthracene-9,10-diethyl ether, and 9,10-bis(n-heptanoyloxy)anthracene. When the present curable composition contains a sensitizer, the content thereof is preferably 0.1 to 10 mass %, more preferably 0.5 to 8 mass %, based on the total mass of the present curable composition. When the content of the sensitizer is within the above range, the curability of the present curable composition becomes good, coloration of the formed cured product is suppressed, and the performance of the cured product tends to be improved.

[0048] In addition to the above-mentioned components, the present curable composition may further contain, if necessary, a polymerization inhibitor such as hydroquinone, di-t-butylhydroquinone, p-methoxyphenol, benzoquinone, dibutylhydroxytoluene, nitrosamine salts, hindered amine compounds, 2,2,6,6-tetramethylpiperidine 1-oxyl (TEMPO), etc. When a polymerization inhibitor is contained, the amount thereof is preferably in the range of 0.01 to 2 mass% based on the total amount of the present curable composition.

[0049] The curable composition may contain additives such as surfactants, ultraviolet absorbers, antioxidants, surface tension regulators, discoloration inhibitors, conductive salts, etc. In order to further improve adhesion to substrates such as plastic substrates, the curable composition may contain non-reactive resins such as acrylic resins, epoxy resins, terpene phenol resins, and rosin esters.

[0050] As described above, the present curable composition contains, as essential components, the (meth)acrylate having a hydroxy group (a), the (meth)acrylate having a phosphate group (b), and the monomer having two or more (meth)acrylate groups (c). From the viewpoints of improving the curability and storage stability of the present curable composition, suppressing coloration and shrinkage of a cured product formed from the present curable composition, and improving performance such as adhesion to a substrate, the present curable composition in an embodiment further containing a (meth)acrylate (d) having a cyclic skeleton is preferred. The above-mentioned (meth)acrylate having a hydroxyl group (a), (meth)acrylate having a phosphoric acid group (b), monomer having two or more (meth)acrylate groups (c), and (meth)acrylate having a cyclic skeleton (d) may be compounds made from biomass raw materials. In this case, the present curable composition itself can be regarded as an environmentally friendly product, which is more preferable from the viewpoint of reducing the environmental load.

[0051] In addition, from the viewpoint of suppressing the shrinkage of the cured product of the present curable composition and improving the performance such as adhesion to the substrate, the ratio of the (meth)acrylate having a cyclic skeleton (d) to the total mass of the polymerizable compound components constituting the present curable composition, that is, the (meth)acrylate having a hydroxyl group (a), the (meth)acrylate having a phosphoric acid group (b), the monomer having two or more (meth)acrylate groups (c), the (meth)acrylate having a cyclic skeleton (d), and other polymerizable compounds contained as necessary, is preferably 30% by mass or more, more preferably 35% by mass or more, more preferably 40% by mass or more, more preferably 45% by mass or more, and even more preferably 50% by mass or more. Such a ratio is preferably 80% by mass or less, more preferably 75% by mass or less, even more preferably 70% by mass or less, even more preferably 65% ​​by mass or less, and particularly preferably 60% by mass or less. In other words, the proportion of the (meth)acrylate (d) having a cyclic skeleton relative to the total mass of the polymerizable compound components constituting the present curable composition is preferably in the range of 30 to 80 mass%, more preferably in the range of 30 to 70 mass%, more preferably in the range of 40 to 70 mass%, more preferably in the range of 50 to 70 mass%, and even more preferably in the range of 50 to 65 mass%. When the proportion of the (meth)acrylate (d) having a cyclic skeleton is within the above range, cure shrinkage during curing of the present curable composition can be reduced, internal stress accumulated in the cured product can be reduced to prevent distortion, and adhesion at the interface between the substrate and the cured product can be better ensured.

[0052] In addition, from the viewpoint of improving the curability of the present curable composition and improving the physical properties such as adhesion of the cured product of the present curable composition to a substrate, the proportion of the monomer (c) having two or more (meth)acrylate groups to the total mass of the polymerizable compound components constituting the present curable composition, i.e., the (meth)acrylate (a) having a hydroxy group, the (meth)acrylate (b) having a phosphoric acid group, the monomer (c) having two or more (meth)acrylate groups, the (meth)acrylate (d) having a cyclic skeleton, and other polymerizable compounds contained as necessary, is preferably 5% by mass or more, more preferably 8% by mass or more, and even more preferably 10% by mass or more. Such a proportion is preferably 65% ​​by mass or less, more preferably 60% by mass or less, more preferably 55% by mass or less, more preferably 50% by mass, more preferably 45% by mass or less, more preferably 40% by mass or less, more preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less. In other words, the proportion of the monomer (c) having two or more (meth)acrylate groups relative to the total mass of the polymerizable compound components constituting the present curable composition is preferably in the range of 5 to 65 mass%, more preferably in the range of 5 to 50 mass%, more preferably in the range of 5 to 45 mass%, more preferably in the range of 5 to 40 mass%, more preferably in the range of 5 to 30 mass%, more preferably in the range of 5 to 20 mass%, and even more preferably in the range of 5 to 15 mass%.

[0053] From the viewpoint of being applicable to a wide range of industrial fields, the present curable composition may further contain an inorganic filler, various pigments, dyes, etc. Examples of the inorganic filler include carbon black, silicas, alumina, titanium oxide, zinc oxide, magnesium oxide, calcium carbonate, talc, etc.

[0054] The present curable composition may further contain a surfactant from the viewpoint of ensuring ease of handling and ejection stability applicable to the inkjet method, and adjusting the surface tension to a desired range. Examples of the surfactant include anionic surfactants such as dialkyl sulfosuccinates, alkyl naphthalene sulfonates, and fatty acid salts; nonionic surfactants such as polyoxyethylene alkyl ethers, polyoxyethylene alkyl allyl ethers, acetylene glycols, and polyoxyethylene-polyoxypropylene block copolymers; and cationic surfactants such as alkylamine salts and quaternary ammonium salts. Furthermore, as the surfactant, preferably hydrophobic organic fluoro compounds such as compounds having a silicone chain, silicone-based surfactants having polyether chains at the side chains or ends and a polysiloxane structure in the main chain, fluorine-based surfactants having perfluoroalkyl chains, oil-like fluorine-based compounds (e.g., fluorine oils), and solid fluorine compound resins (e.g., tetrafluoroethylene resins) may be used. When the present curable composition further contains a surfactant, the content thereof is preferably from 0.05 to 1 mass %, and more preferably from 0.1 to 0.8 mass %, based on the total mass of the present curable composition.

[0055] The present curable composition may further contain a leveling agent. The leveling agent is easy to smooth the surface of the cured product formed from the curable composition, so that the cured product is easily cured uniformly when irradiated with ultraviolet light, and therefore the cured product is less likely to have unevenness. Examples of the leveling agent include silane compounds, fluorine compounds, acrylic copolymers, and alcohol alkoxylate compounds. The above-mentioned surfactants can also be used as the leveling agent.

[0056] The viscosity of the present curable composition at 25°C is preferably in the range of 3 to 30 mPa·s, more preferably in the range of 5 to 20 mPa·s. The surface tension of the present curable composition is preferably in the range of 15 to 45 mN / m, more preferably in the range of 20 to 40 mN / m, and even more preferably in the range of 25 to 35 mN / m. It is preferable that the viscosity and surface tension of the present curable composition at 25°C are within the above ranges from the viewpoints of improving the handleability of the present curable composition and the inkjet discharge stability when molding by an inkjet method. Here, the present curable composition may further contain a solvent for the purpose of adjusting the viscosity as described above, within a range that does not impair the effects of the present invention, but it is preferable that the present curable composition does not contain a solvent. When the present curable composition does not contain a solvent, a drying step or a heat treatment (annealing treatment) for removing the solvent can be omitted when curing the present curable composition, and the manufacturing process can be simplified. In addition, the present curable composition has good curability, and outgassing derived from the solvent is unlikely to occur from the cured product, which tends to improve safety. Therefore, it is easy to obtain the present curable composition that can be applied by the inkjet method and does not require annealing treatment.

[0057] The present curable composition can be produced by, for example, using a conventional dispersing machine such as a bead mill or a stirrer, supplying and stirring and mixing the above-mentioned (meth)acrylate having a hydroxyl group (a), (meth)acrylate having a phosphate group (b), monomer (c) having two or more (meth)acrylate groups, (meth)acrylate having a cyclic skeleton (d), and various optional additional components as necessary. As the dispersing machine, in addition to a bead mill, various known and commonly used dispersing machines such as an ultrasonic homogenizer, a high-pressure homogenizer, a paint shaker, a ball mill, a roll mill, a sand mill, a sand grinder, a Dyno Mill, a Dispermat, an SC Mill, or a Nanomizer can be used.

[0058] As described above, the present curable composition is preferably a curable composition that is cured by active energy rays. Examples of active energy rays include visible light, ultraviolet rays, infrared rays, microwaves, EUV, semiconductor laser light, and excimer lasers (KrF, ArF). Among these active energy rays, the present curable composition is more preferably a curable composition that is cured by irradiation with light such as ultraviolet rays. Examples of light sources that can be used for ultraviolet rays include metal halide lamps, xenon lamps, carbon arc lamps, chemical lamps, low-pressure mercury lamps, high-pressure mercury lamps, UV-LED lamps, etc. From the viewpoint of extremely low heat generation and environmental protection that can accommodate mercury-free products, it is more preferable to cure the composition by light irradiation using a UV-LED lamp as a light source, preferably a UV-LED lamp with a main peak wavelength of approximately 365 to 405 nm that can provide sufficient illuminance. The irradiation energy of UV-LED light is 50-3000mJ / cm 2 and preferably in the range of 200 to 2000 mJ / cm 2 The range is more preferable.

[0059] The method of sealing a light-emitting element using the present curable composition as a sealant is not particularly limited. For example, the present curable composition is dropped onto a light-emitting element, or applied via a spin coater, a die coater, a dispenser, an inkjet method, a stencil printing method, a screen printing method, a gravure printing method, or a mask, and then cured; the present curable composition is injected into a mold formwork in advance, for example, by a dispenser, transfer molding, injection molding, etc., and a lead frame or the like to which a light-emitting element is fixed is immersed therein, and then cured; the present curable composition is injected into a formwork into which a light-emitting element is inserted, and then cured; and the present curable composition is injected into a cup or the like with a dispenser or the like, at the bottom of which a light-emitting element is disposed, and then cured. Alternatively, the present curable composition may be applied onto a release film using a coater or the like to a thickness ranging from the order of submicrons (0.1 μm) to the order of several hundred μm, and then partially cured to form a semi-cured film or sheet. The semi-cured film or sheet may be transferred onto a substrate on which a light-emitting element is fixed, and then cured again to seal the light-emitting element.

[0060] Among them, molding by an inkjet method using an inkjet recording method is preferred. In this case, droplets of the present curable composition can be landed on the target with good positional accuracy, so that the accuracy of the shape and dimensions of the cured product can be improved. In addition, compared with molding by a printing method involving contact such as a screen printing method, when the present curable composition is molded by the inkjet method, foreign matter is less likely to be mixed into the present curable composition and its cured product, and the yield is less likely to be reduced when manufacturing a sealed light-emitting device. As the inkjet recording method, any of the conventionally known methods can be used, such as a method of ejecting droplets by utilizing the vibration of a piezoelectric element (a recording method using an inkjet head that forms ink droplets by the mechanical deformation of an electrostrictive element) or a method that utilizes thermal energy.

[0061] The present curable composition is preferably ejected by an inkjet method, molded, and then cured by irradiation with active energy rays, preferably ultraviolet rays, to produce a cured product. The present curable composition is suitable as a composition for sealing a light-emitting element such as an organic EL element or an LED element, and is more suitable as a composition for an LED sealing material. That is, one embodiment of the present invention is an LED element including a cured product of the present curable composition. In particular, the present curable composition can be suitably used as a sealing material for a micro LED element. In addition, an electronic device using a cured product of the present curable composition is also an aspect of the present invention. By using the cured product of the present curable composition, the precision of the dimensions and shape of the electronic device can be improved, and the physical properties of the cured product of the present curable composition can be exhibited. Examples of such electronic devices include displays using light-emitting elements such as LED elements, micro LED elements, organic EL elements, and organic light-emitting elements (OLEDs), mobile terminals, watches, monitors and other display devices, touch panels, and lighting; conductive films, organic semiconductor devices, solar cells, organic solar cells, organic photoconductors (OPCs), organic transistors, and the like.

[0062] The present curable composition can also be used to produce a cured product having an uneven shape such as a lens shape, etc. In other words, an optical element using the cured product of the present curable composition is also one embodiment of the present invention. Examples of such optical elements include light guide plates having microlenses formed on the surface in liquid crystal backlight devices, mobile terminals such as smartphones, etc. By using a cured product of the present curable composition, the precision of the dimensions and shape of the optical element can be improved, and the physical properties of the cured product of the present curable composition can be exhibited. Specifically, the present curable composition is ejected by an inkjet method, molded, and then irradiated with active energy rays to cure, thereby producing a microlens with excellent dimensional accuracy of the lens diameter and lens height on the order of 10 μm. Alternatively, an electroformed mold can be produced from a microlens master plate using a cured product of the present curable composition, and the electroformed mold can be used to produce a molded product (optical element) having a microlens microstructure on its surface.

[0063] The applications of the present curable composition are not limited to the above-mentioned electronic devices and optical elements, and the present curable composition can be used to manufacture various products that utilize its properties.

[0064] An example of the configuration of a micro LED display, which is an electronic device using a cured product of the present curable composition, is shown in Fig. 1. However, the present curable composition can be applied to, for example, displays disclosed in U.S. Patent Registration No. 10978626. In FIG. 1, the micro LED display 100 includes a substrate 2, a micro LED element 1 disposed on the substrate 2, an encapsulant 3, a joint 4 between the micro LED element 1 and a metal wiring portion (not shown) formed on the surface of the substrate 2, a partition 5, and a black layer 6 covering the upper portion of the partition 5. The micro LED display 100 includes a plurality of micro LED elements 1, and adjacent micro LED elements 1 are separated by partition walls 5 on a substrate 2. The encapsulant 3 is a cured product of the present curable composition. For example, a film made of a transparent inorganic material such as glass, or a heat-resistant resin material such as polyethylene naphthalate, polyamide, polyimide, etc. can be used as the substrate 2. The thickness of the substrate 2 is not particularly limited, and in terms of a balance between heat resistance, insulation properties, manufacturing costs, etc., the thickness of the substrate 2 is usually preferably in the range of 25 to 125 μm in the case of a film.

[0065] The micro LED display 100 can be manufactured, for example, as follows. First, a substrate 2 is prepared, and a plurality of micro LED elements 1 are mounted on one surface of the substrate 2. Next, a partition wall 5 is formed on one surface of the substrate 2, for example, by a photolithography method or an inkjet method using a photosensitive resin material. Then, the present curable composition is molded, for example, by an inkjet method, to form a coating film, and then the coating film of the present curable composition is irradiated with ultraviolet light to be cured, thereby producing the encapsulant 3. The coating film of the present curable composition may be irradiated with ultraviolet light in an oxygen-containing atmosphere such as air, or in an inert atmosphere such as a nitrogen atmosphere. The thickness of the encapsulant 3 in the micro LED display 100 is preferably in the range of 5 to 100 μm, more preferably in the range of 10 to 50 μm. By making the encapsulant 3 thinner, the micro LED display 100 can be made thinner and flexibility can be imparted. The thickness of the encapsulant 3 refers to the distance from the outermost surface of the encapsulant 3 or the interface with the opposing substrate to the outermost surface on the other side of the surface or the opposing interface.

[0066] Although an embodiment of the present curable composition, the cured product of the present curable composition, the LED element containing the cured product, and the electronic device using the cured product have been described above, the present invention is not limited to the configuration of the above-mentioned embodiment. For example, the present curable composition may have any other configuration in addition to the configuration of the above embodiment, or may be replaced with any configuration that produces a similar effect. EXAMPLES

[0067] EXAMPLES The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these examples. The compounds used in the present examples are shown below.

[0068] <(Meth)acrylate (a) Having a Hydroxy Group> a-1: 4-HBA (trade name, manufactured by Osaka Organic Chemical Industry Co., Ltd., 4-hydroxybutyl acrylate) a-2: HPA (product name, manufactured by Osaka Organic Chemical Industry Co., Ltd., hydroxypropyl acrylate) a-3: Miramer M340 (product name, manufactured by MIWON, pentaerythritol triacrylate) <(Meth)acrylate having a phosphoric acid group (b)> b-1: KAYAMER PM-2 (product name, manufactured by Nippon Kayaku Co., Ltd.) b-2: Light Acrylate P-1A(N) (trade name, manufactured by Kyoeisha Chemical Co., Ltd., 2-acryloyloxyethyl acid phosphate) <Monomer (c) Having Two or More (Meth)acrylate Groups> c-1: Miramer M240 (product name, manufactured by MIWON, ethylene oxide modified bisphenol A diacrylate) c-2: Miramer M3130 (trade name, manufactured by MIWON, trimethylolpropane ethylene oxide modified triacrylate) c-3: Miramer M210 (trade name, manufactured by MIWON, hydroxypivalic acid neopentyl glycol diacrylate) c-4: Miramer M360 (trade name, manufactured by MIWON, trimethylolpropane propylene oxide adduct triacrylate) <(Meth)acrylate having a cyclic skeleton containing a hetero atom (d1)> d1-1: Viscoat 150 (trade name, manufactured by Osaka Organic Chemical Industry Co., Ltd., tetrahydrofurfuryl acrylate) d1-2: Viscoat 200 (product name, manufactured by Osaka Organic Chemical Industry Co., Ltd., cyclic trimethylolpropane formal acrylate) <(Meth)acrylate having a carbon ring skeleton (d2)> d2-1: Light Acrylate PO-A (product name, manufactured by Kyoeisha Chemical Co., Ltd., phenoxyethyl acrylate) d2-2: Isobornyl acrylate (Osaka Organic Chemical Industry Co., Ltd.) d2-3: Viscoat 196 (product name, manufactured by Osaka Organic Chemical Industry Co., Ltd., 3,3,5-trimethylcyclohexyl acrylate) d2-4: Miramer M1150 (product name, manufactured by MIWON, t-butylcyclohexyl acrylate) <Photopolymerization initiator> TPO-H: (2,4,6-trimethylbenzoyl)diphenylphosphine oxide; (IGM RESINS BV) Omnirad 819: Phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (acylphosphine oxide series; manufactured by IGM RESINS BV) <Polymerization inhibitor> Nonflex Alba: 2,5-di-t-butylhydroquinone (Seiko Chemical Co., Ltd.) <Additives (Leveling Agents)> KF-352: Polyether modified polysiloxane (manufactured by Shin-Etsu Chemical Co., Ltd.)

[0069] Manufacturing Examples 1-21 1. Preparation of the Curable Composition According to the blending ratios shown in Table 1, each component was placed in a container and mixed with stirring to prepare curable compositions 1 to 21.

[0070] 2. Evaluation 2-1. Viscosity of the curable composition The viscosity was measured using an E-type viscometer (TVE-25L, manufactured by Toki Sangyo Co., Ltd.) at a temperature of 25° C. The viscosity of each curable composition is shown in Table 1 using the following evaluation index. [Evaluation index] A: 20 mPa·s or less. B: More than 20 mPa·s and less than 30 mPa·s. C: More than 30 mPa·s. Furthermore, when each of the curable compositions was stored at −20 to 20° C., the change in viscosity was small, and all of them had good storage stability.

[0071] 2-2.Light transmittance of cured product (1) The curable composition obtained in each manufacturing example was applied to a non-alkali glass substrate (length 35 mm × width 35 mm, thickness 0.7 mm) with a thickness of 10 μm using a spin coater to form a coating film. This coating film was then irradiated with a UV-LED irradiation device (manufactured by ITEC Systems Co., Ltd.) at a peak wavelength of 385 nm and a peak irradiance of 500 mW / cm. 2 , Accumulated light intensity 3J / cm 2 The coating was cured by irradiating ultraviolet light under the conditions shown in Table 1 to produce a cured product (cured coating film). Each of the cured products was almost transparent. (2) The light transmittance of each of the cured products obtained above at wavelengths of 400 to 800 nm was measured using a spectrometer ("LCD-5200" manufactured by Otsuka Electronics Co., Ltd.) The measured light transmittance of only the alkali-free glass substrate used in producing the cured products was used as a reference value. The light transmittance at 550 nm of each cured product is shown in Table 1.

[0072] 2-3.Adhesion of the cured product In the same manner as in 2-2(1), a cured product (cured coating film) of the curable composition obtained in each production example was prepared, and a cross-shaped cut was made on the surface of the cured product using a cutter. Then, an adhesive tape (manufactured by Nichiban Co., Ltd.) was applied on the cross-shaped cut and then peeled off. Furthermore, a new adhesive tape was applied to the same cross-shaped cut as above and the operation of peeling it off was repeated five times in total. After each operation, the adhesive tape was peeled off and the cured coating film was visually observed to see whether it had peeled off from the alkali-free glass substrate, and the adhesion was evaluated as follows. [Evaluation Criteria] A: There was no peeling of the cured coating film. B: Peeling of the cured coating occurred after the third application. C: Peeling of the cured coating film was observed after the first or second application.

[0073] 2-4.Heat resistance of the cured product In the same manner as in 2-2(1), a cured product (cured coating film) was prepared from the curable composition obtained in each production example. Each cured product was placed in a clean oven (manufactured by ESPEC) at 120°C and aged for 500 hours, and the light transmittance after aging was measured in the same manner as in 2-2. From the measurement results of the light transmittance spectrum, * The heat resistance was evaluated according to the following criteria. * indicates the degree of change in color tone, with a larger positive value meaning a stronger yellow tone. [Evaluation Criteria] A: 0≦b * <1 B:1≦b * <2 C:2≦b *

[0074] 2-5. Light resistance of the cured product In the same manner as in 2-2(1), a cured product (cured coating film) was prepared from the curable composition obtained in each production example, and the cured product was measured using a Suntest device (ATLAS Material Testing Technology GmbH, CPS+, 765 W / m 2 Each cured product was placed in a 350-degree C (50°C) and irradiated with sunlight equivalent to sunlight for 500 hours. The light transmittance after irradiation was measured using the procedure in 2-2, and b was calculated from the difference in light transmittance before and after irradiation. * The light resistance was evaluated according to the following criteria. * The meaning is the same as 2-4. [Evaluation Criteria] A: 0≦b * <1 B:1≦b * <2 C:2≦b *

[0075] 2-6. Moisture resistance of the cured product In the same manner as in 2-2(1), a cured product (cured coating film) was prepared from the curable composition obtained in each production example, and each cured product was placed in a thermostatic chamber at 85°C and a relative humidity of 85% for 500 hours. After removing the cured product and allowing it to cool naturally to 25°C, the surface was observed under a microscope (magnification 100x) for the presence or absence of non-uniformity, and the moisture resistance was evaluated according to the following criteria. [Evaluation Criteria] A: No change B: Non-uniformity was observed on the surface of the cured product in some areas. C: The non-uniformity of the cured surface can be confirmed visually without the need for microscopic observation.

[0076] The blending ratio of the curable composition and the above-mentioned evaluation results are summarized in Table 1. Table 1 also shows the ratio of the monomer (c) having two or more (meth)acrylate groups to the total mass of the polymerizable compounds (monomer (c) ratio; mass %) and the ratio of the (meth)acrylate (d) having a cyclic skeleton to the total mass of the polymerizable compounds ((meth)acrylate (d) ratio; mass %) in the curable composition of each Production Example.

[0077] [Table 1]

[0078] From these results, when the curable composition contains the (meth)acrylate (a) having a hydroxyl group and the monomer (c) having two or more (meth)acrylate groups as essential components and does not contain the (meth)acrylate (b) having a phosphoric acid group, if it further contains the (meth)acrylate (d) having a cyclic skeleton, the curing property is excellent, and the cured product has excellent transparency, adhesion to the substrate, heat resistance, light resistance, and moisture resistance. In particular, when the ratio of the (meth)acrylate (d2) having a carbon ring skeleton in the (meth)acrylate (d) having a cyclic skeleton is 50 mass% or more, the heat resistance of the obtained cured product is more excellent (Production Examples 13 to 21). Furthermore, when the curable composition contains, as essential components, a (meth)acrylate having a hydroxyl group (a), a (meth)acrylate having a phosphate group (b), and a monomer having two or more (meth)acrylate groups (c), when the (meth)acrylate having a hydroxyl group (a) is 10 mass% or more and the (meth)acrylate having a phosphate group (b) is 0.01 mass% or more relative to the total mass of the curable composition, a curable composition can be obtained that exhibits particularly good adhesion to a substrate of the cured product (Production Examples 1 to 8). Furthermore, preferably, when the ratio of the (meth)acrylate having a cyclic skeleton (d) to the total mass of the polymerizable compound components constituting the curable composition, i.e., the above-mentioned (meth)acrylate having a hydroxy group (a), the (meth)acrylate having a phosphate group (b), the monomer (c) having two or more (meth)acrylate groups, the (meth)acrylate having a cyclic skeleton (d), and other polymerizable compounds further contained as necessary, is in the range of 30 to 80 mass%, the obtained cured product has excellent and balanced properties in terms of the above-mentioned various physical properties such as adhesion to a substrate, heat resistance, light resistance, and moisture resistance. [Industrial Applicability]

[0079] The curable composition of the present invention has excellent curability, can be formed into a molded product by an inkjet method, and has excellent physical properties such as heat resistance, light resistance, moisture resistance, and transparency. The curable composition of the present invention is particularly suitable as a composition for an LED encapsulant, and is useful as an encapsulant for micro LED elements. In addition, electronic devices using the cured product of the present curable composition are useful as various display devices, touch panels, or lighting; conductive films, organic semiconductor devices, solar cells, organic solar cells, organic photoconductors (OPCs), organic transistors, and the like. Optical elements using the cured product of the present curable composition are useful as components of mobile terminals such as liquid crystal backlight devices and smartphones. [Explanation of symbols]

[0080] 1. Micro LED element 2. Board 3. Encapsulating material 4 Joint 5 Bulkhead 6 Black layer 100 Micro LED Display

Claims

1. A curable composition comprising, as essential components, a (meth)acrylate having a hydroxyl group (a), a monomer having two or more (meth)acrylate groups (c), and a (meth)acrylate having a cyclic skeleton (d), wherein the monomer having two or more (meth)acrylate groups (c) is contained in an amount of 5 to 50 mass% based on the total mass of the composition, the monomer having two or more (meth)acrylate groups (c) is contained as a monomer having three or more (meth)acrylate groups, and the (meth)acrylate having a cyclic skeleton (d) is one or more selected from the group consisting of (meth)acrylates having a cyclic skeleton containing a hetero atom (d1) and (meth)acrylates having a carbon ring skeleton (d2), and the curable composition comprises 30 to 80 mass% based on the total mass of the composition.

2. The curable composition according to claim 1 , further comprising (b) a (meth)acrylate having a phosphoric acid group.

3. The curable composition according to claim 1 or 2, wherein the (meth)acrylate (a) having a hydroxy group is contained in an amount of 10 to 50 mass % based on the total mass of the composition.

4. The curable composition according to claim 2, wherein the (meth)acrylate (b) having a phosphoric acid group is contained in an amount of 0.01 to 10% by mass based on the total mass of the composition.

5. The curable composition described in claim 1 or 2, wherein the (meth)acrylate having a carbon ring skeleton (d2) is a monofunctional (meth)acrylate having a cyclic aliphatic group.

6. The curable composition according to claim 1 or 2, further comprising a photopolymerization initiator.

7. The curable composition according to claim 1 or 2, which is an active energy ray-curable composition.

8. The curable composition according to claim 1 or 2, having a viscosity at 25° C. of 3 to 30 mPa·s.

9. The curable composition according to claim 1 or 2, which does not contain a solvent.

10. The curable composition according to claim 1 or 2, which is a composition for an LED encapsulant.

11. The curable composition according to claim 1 or 2, which is formed by an ink-jet method.

12. A cured product of the curable composition according to claim 1 or 2.

13. The cured product according to claim 12, which is an LED encapsulant.

14. An LED element comprising a cured product of the curable composition according to claim 1 or 2.

15. An electronic device using a cured product of the curable composition according to claim 1 or 2.

16. An optical element comprising a cured product of the curable composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Photosensitive resin composition

    JP1994001906A

  • Organic electroluminescent element and manufacture thereof

    JP2000223264A

  • Photo-curable resin composition and adhesive for optical discs

    JP2006124549A

  • Inkjet drawing method and recording material

    JP2013215940A

  • Active energy ray-curable ink, active energy ray-curable process liquid, and inkjet recording method

    JP2014058622A